2020
DOI: 10.1128/jvi.02134-19
|View full text |Cite
|
Sign up to set email alerts
|

Elongin C Contributes to RNA Polymerase II Degradation by the Interferon Antagonist NSs of La Crosse Orthobunyavirus

Abstract: Mosquito-borne La Crosse virus (LACV; genus Orthobunyavirus, family Peribunyaviridae, order Bunyavirales) causes up to 100 annual cases of severe meningoencephalitis in children and young adults in the United States. A major virulence factor of LACV is the nonstructural protein NSs, which inhibits host cell mRNA synthesis to prevent the induction of antiviral type I interferons (IFN-α/β). To achieve this host transcriptional shutoff, LACV NSs drives the proteasomal degradation of RPB1, the large subunit of mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
0
6
0
1
Order By: Relevance
“…The three negative-sense, single-stranded RNA genome segments of LACV each have defined roles in virus pathogenesis. The S segment encodes a virulence factor, NSs, that efficiently inhibits the interferon system of infected mammalian hosts; its absence results in reduced virulence in mice [ 12 , 13 , 14 ]. In at least one instance, neurovirulence mapped to the L segment, which encodes the viral polymerase [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The three negative-sense, single-stranded RNA genome segments of LACV each have defined roles in virus pathogenesis. The S segment encodes a virulence factor, NSs, that efficiently inhibits the interferon system of infected mammalian hosts; its absence results in reduced virulence in mice [ 12 , 13 , 14 ]. In at least one instance, neurovirulence mapped to the L segment, which encodes the viral polymerase [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were also found when studying LACV [ 84 ]; moreover, this study additionally found that NSs served as a virulence factor only in mammalian cells, with no NSs-related inhibitory activity found in mosquito cells. It should also be noted that NSs of BUNV, LACV, and the related Schmallenberg (SBV) virus were all found to localize to the nucleus of infected cells to inhibit transcription initiation by RNA polymerase II and disrupt nucleoli [ 78 , 85 , 86 , 87 ]. The NSs of Rift Valley fever virus (RVFV), which also interferes with IFN induction and RNA polymerase II activity [ 79 , 88 , 89 ], additionally plays a role in inhibiting mRNA transport [ 90 ].…”
Section: Factors Affecting Bunyavirus Replication-viral Factorsmentioning
confidence: 99%
“…Similar results were also found when studying LACV [74]; moreover, this study additionally found that NSs served as a virulence factor only in mammalian cells, with no NSs-related inhibitory activity found in mosquito cells. It should also be noted that NSs of BUNV, LACV and the related Schmallenberg (SBV) virus localize to the nucleus of infected cells, to inhibit transcription initiation by RNA polymerase II and disrupt nucleoli [75][76][77][78]. The NSs of Rift Valley fever virus (RVFV), which also interferes with IFN induction and RNA polymerase II activity [79][80][81], additionally plays a role in inhibiting mRNA transport [82].…”
Section: Nssmentioning
confidence: 99%